STRATEGI PENDAPATAN UNIVERSITAS MELALUI PUSAT BISNIS - Taufan, Januar; Sarwoko, Haris (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
The purpose of this research is to explain what was done in building a university business center to be taken into consideration by other parties in developing a university business center. This research method is participatory action research, with primary data taken for three months, strengthened by researchers directly involved in making the concept, planning, and execution of the business center daily. This study finds that X University Business Center Team' strategies are data collection, human resources strengthening, and development. The main challenge faced in managing the X University business center is the lack of support from all parties and both internal and external communication problems. The novelty of this research is to fill in the gaps in a structured scientific study of university financial management that is much needed.. Keywords : college income; business center; university finance; governance